2018
DOI: 10.1371/journal.pone.0194059
|View full text |Cite
|
Sign up to set email alerts
|

Mating system and extra-pair paternity in the Fan-tailed Gerygone Gerygone flavolateralis in relation to parasitism by the Shining Bronze-cuckoo Chalcites lucidus

Abstract: Extra-pair copulation can increase genetic diversity and offspring fitness. However, it may also increase intra-nest variability in avian hosts of brood parasites, which can decrease the discrimination ability of host parents towards the parasite. In New Caledonia, the Fan-tailed Gerygone (Gerygone flavolateralis), which is parasitized by the Shining Bronze-cuckoo (Chalcites lucidus), has two nestling morphs, dark and bright, that can occur in monomorphic and polymorphic broods. Gerygone parents recognize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Thus, nestling phenotypes may change if parents exchange partners or incur in extra-pair copulations and this may strongly constrain the selective advantage of nestling polymorphism as a host defence. In the Fan-tailed Gerygone, extra-pair copulations had however no impact on the frequency of nestling or brood types 39 . Nevertheless, polymorphic broods may have further promoted the arms race, which involves generalist mimicry by the parasite and true-recognition based on multiple sensorial cues by the host.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, nestling phenotypes may change if parents exchange partners or incur in extra-pair copulations and this may strongly constrain the selective advantage of nestling polymorphism as a host defence. In the Fan-tailed Gerygone, extra-pair copulations had however no impact on the frequency of nestling or brood types 39 . Nevertheless, polymorphic broods may have further promoted the arms race, which involves generalist mimicry by the parasite and true-recognition based on multiple sensorial cues by the host.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to Australian Gerygone species, Fan-tailed Gerygone have two distinct nestling morphs, with a pinkish-grey (bright) or a darkish-brown (dark) skin, which can occur in monomorphic and polymorphic broods 37 , 39 . Brood colouration can vary within broods of the same parents, however it is most often constant for the same pair across multiple breeding attempts and extra-pair copulations do not influence the proportions of bright, dark or polymorphic broods 39 . The Shining Bronze-cuckoo from New Caledonia also has two nestling morphs, dark and bright 37 .…”
Section: Introductionmentioning
confidence: 97%
“…Pairs of the fan‐tailed gerygone are socially monogamous and use the same territory over several breeding seasons (Bojarska et al , Attisano et al ). The average clutch size is 2.1 ± 0.1 (all averages with 95% confidence intervals) eggs, the incubation phase is 18 ± 1 days and the nestling phase is 14 ± 1 days (Attisano et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies using molecular techniques have revealed that social monogamy does indeed not necessarily imply genetic monogamy: while 90% of bird species are socially monogamous (Cockburn 2006), out of these, less than 25% are also genetically monogamous (reviewed in Griffith et al 2002, Bojarska et al 2018. In comparison, monogamy in mammals is less common and only 3-9% of the species are defined as socially monogamous (Trivers 1972, Lukas and.…”
Section:   mentioning
confidence: 99%